Pelatihan Basic Reservation & Ticketing System di SMKN 1 Tambun Selatan, Bekasi, Jawa Barat - Aisyah Rahmawati; Vica N Harahap; Abdul Ghafar; Sandriana Marina; Lira Agusinta (Institut Transportasi dan Logistik Trisakti, 2021)
SMKN 1 Tambun Selatan is a vocational high school based on management industry and has 4 (four) majors, namely: Tourism; Hospitality; Office administration; and Catering. In the curriculum, in the Department of Tourism there are Reservation and Ticketing subjects which are part of the pre-flight service in flight services. Bookkeeping service activities (reservation) and issuance of passenger tickets (ticketing), must be carried out carefully and precisely. Vocational students' skills in understanding reservation and ticketing materials need to be supported by practicing using a simulation application from the Global Distribution System (GDS) as an airline distribution channel. Practical activities require internet technology-based facilities which are usually located in a room called a laboratory. These skills will increase the competence of students at SMKN 1 Tambun Selatan which is required by the Industrial World. However, currently the school does not have a laboratory as a facility that supports the creation of student competencies. This is a problem for schools to be able to complete the competence of their students. The practical training method for the reservation and ticketing system simulation provided by the Trisakti Transportation and Logistics Institute (ITL) Lecturers is a solution in introducing the flight service system for students of SMKN 1 Tambun Selatan who currently do not have reservation or ticketing system facilities in the school laboratory. The results of the training evaluation showed that students were able to increase their knowledge after attending the training and were satisfied with this training activity.